Billy Budd, Sailor and other stories - Melville, Herman, 1819-1891. (New York : Bantam Books, 1984)
A collection of six short stories by the author of "Moby Dick.".
Billy Budd, Sailor -- The piazza -- Bartleby -- Benito Cereno -- The encantadas -- The bell-tower.
Young Adult
Keywords: Short stories